OpenMP in the petascale era 7th International Workshop on OpenMP, IWOMP 2011, Chicago, IL, USA, June 13-15, 2011. Proceedings - Chapman, Barbara 1954- (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 7th International Workshop on OpenMP, IWOMP 2011, held in Chicago, IL, USA in June 2011. The 13 revised full papers presented were carefully reviewed and selected for inclusion in the proceedings. The papers are organized in topical sections on using OpenMP with application, tools for OpenMP, extensions of OpenMP, and implementation and performance.